Integrative Neuromuscular Training in Adolescents and Children Treated for Cancer (INTERACT): Study Protocol for a Multicenter, Two-Arm Parallel-Group Randomized Controlled Superiority Trial - Schmidt-Andersen, Peter; Fridh, Martin Kaj; Müller, Klaus Gottlob; Anna Pouplier,; Hjalgrim, Lisa Lyngsie; Faigenbaum, Avery D.; Schmiegelow, Kjeld; Hasle, Henrik; Lykkedegn, Sine; Zhang, He; Christensen, Jan; Larsen, Hanne Bækgaard (Frontiers in Pediatrics, 2022)
Background: Improved survival rates for children and adolescents diagnosed with cancer call for novel strategies for reducing short- and long-term treatment-related side effects. These include the physical and metabolic sequelae that are exacerbated by sedentary behavior and treatment-induced toxicities. We aim to investigate the effect of an integrative neuromuscular training intervention during the first six months of anti-cancer treatment primarily on muscle strength, and secondarily on exercise capacity, physical function, markers of metabolic syndrome, dysmetabolism, and health-related quality of life during and after ended treatment. Methods: One hundred and twenty-seven children and adolescents, newly diagnosed with malignant and benign neoplasia, aged 6–17 years, and treated with chemotherapy or radiation will be randomized to either the intervention or the control arm of the study. The intervention group will, in addition to usual care, be offered a combination of 6 months of supervised physical exercise (integrative neuromuscular training) and home-based exercise. The active control group will, in addition to usual care, receive information along an unsupervised written home-based training program. All participants, including parents, will receive information about the importance of physical exercise during the course of cancer treatment, at the start of treatment, and in five monthly sessions. The primary outcome is measured in terms of isometric quadriceps muscle strength. Secondary outcomes include muscle strength and endurance, markers of metabolic syndrome and dysmetabolism, exercise capacity, physical function and activity, days of hospitalization, and health-related quality of life. Assessment will be conducted at treatment initiation (baseline), at 3 and 6 months after inclusion, and 1 month and 1 year after ended treatment. The primary endpoint for lower-body muscle strength is at 6 months after treatment initiation. The effects of the intervention will be evaluated through a constrained linear mixed model. Discussion: This national randomized controlled study has the potential to provide new knowledge concerning the short- and long-term effects of a novel, inclusive approach for youth exercise programming (integrative neuromuscular exercise) in children and adolescents during anti-cancer treatment. Using a pragmatic, low-cost, and time-efficient training design, this intervention can be easily adapted to both hospital and home settings.